Revolutionizing STEM Education: Unleashing the Potential of STEM Interest Careers in Malaysia - Rashidin Idris; Priyalatha Govindasamy; Suppiah Nachiappan; Juppri Bacotang (Human Resource Management Academic Research Society (HRMARS), 2023)
STEM education and STEM oriented occupations have emerged as major drivers of talent pool expansion, economic growth, and technical advancement in Malaysia's dynamic terrain, where innovation and progress reign supreme. Malaysia recognises the critical need to create a solid talent pool capable of navigating this fast evolving terrain as the globe becomes increasingly reliant on science, technology, engineering, and mathematics. STEM education, with its multidisciplinary approach that integrates these important disciplines, has become the cornerstone of Malaysia's educational system, empowering a generation of STEM-literate persons ready to face the future's problems and opportunities. Simultaneously, the appeal of STEM interest employment has grabbed aspirant persons, providing avenues that merge enthusiasm and proficiency, ensuring Malaysia remains at the forefront of global innovation. We delve into the domains of STEM education and STEM oriented careers in Malaysia, finding their transformative impact on nurturing and extending the nation's talent pool, boosting economic competitiveness, and propelling scientific and technological brilliance in this enthralling exploration.